A comparative study of Fistulotomy and Sclerosing Agents in the management of perianal fistula: A randomized controlled clinical - Monireh Sadat Hosseini Rad; Mohsen Najmodini; Mohammad Reza Ghasemian Moghaddam (مجله دانشگاه علوم پزشکی بیرجند, 2023)
Background and Aims: The perianal fistula is a pathological tract between two epithelial surfaces of the anorectal canal and perianal skin. The most common treatment method is fistulotomy which leads to complications, such as incontinency. The present is study aimeds to compare the results of fistulotomy surgery and sclerotherapy in the management of managing the perianal fistula. Materials and Methods: This Randomized controlled clinical study was performed on 24 patients with anorectal fistula. The procedure performed for group 1 was surgical fistulotomy, and group 2 underwent sclerosant agent injection. Recovery time, recurrence rate, post-operative pain, and degree of incontinency were evaluated. The statistical analysis was performed in SPSS software (Version 18), and a p-value less than 0.05 was considered statistically significant. Results: There were 5 (41.7%) men and 7 (58.3%) women in the sclerosing group, as well as 7 (58.3%) men and 5 (41.7%) women in the fistulotomy group. There was no significant relationship between the two groups (P=0.68). The recurrence rate was 3 cases (42.9%) in sclerosing group and 4 cases (57.1%) in the fistulotomy group, which was not statistically significant (P=0.65). The fecal continency score after sclerotherapy was greater than that in the fistulotomy group (P<0.05), and the length of hospitalization, post-surgery discomfort, and the time it took for the fistula to heal were all considerably shorter in the sclerosing group. Conclusion: We concluded that injectable sclerotherapy is effective, safe, simple, acceptable and affordable in the treatment of perianal fistula.